(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2017)
The paper provides a brief bio-bibliographical background of the French author Alain Robbe-Grillet and analyses in depth the basic principles of the ‘New French Novel’. It accounts for its conventional time and space breach and looks into its presence in his first two novels; The erasers and Jealousy, which still bear some traces of the detective fiction. This literary analysis exposes their hybrid and postmodern character and the growing parody being made of the police genre.